Genotoxic and Cytotoxic Effects of Belomycin and Crud Extracts of Mirabilis jalapa Linn in Male White Mice - WAGDI SABEEH SADEQ; SHIREEN ABED AL-RAZAQ TAHA (Tikrit Journal of Pure Science)
Genotoxicity and cytotoxicity of Belomycin (BLM) have been evaluated in bone-marroww cells by micronucleus test, as well as the analysis of sperm shape abnormalities in male white mice, considering that BLM is the most wide anticancer drug used with patients. Also, the study includes assessment the effect of crude water and alcoholic extracts of the four o'clock flowers (Mirabilis jalapa Linn) in reducing BLM toxicity and the study was carried out  in the Genetics Laboratory of the Department of biology for the period from 1-10-2017 to 1-5-2019.So the genotoxicity and cytotoxicity were evaluated independently and in conjunction between two different dosages of BLM 0.8 and 1.6 mg.kg-1.bwt. and three orally dosage of different concentration of crud extracts, which is 39.8, 26.52, 13.26 mg.kg-1 and 7.02, 4.68, 2.34 mg.kg-1 o water and alcohol extract respectively.